1989
DOI: 10.1002/j.1537-2197.1989.tb11366.x
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Organ Initiation and Common Primordia in Flowers of Pisum Sativum (Leguminosae: Papilionoideae)

Abstract: The floral ontogeny of Pisum sativum shows a vertical order of succession of sepals, petals plus carpel, antesepalous stamens, and antepetalous stamens. Within each whorl, unidirectional order is followed among the organs, beginning on the abaxial side of the flower, as in most papilionoids. Unusual features include the four common primordia which precede initiation of discrete petal and antesepalous stamen primordia, and the marked overlap of organ initiations between whorls which are usually separately initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
0
6

Year Published

1990
1990
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 27 publications
(25 reference statements)
3
78
0
6
Order By: Relevance
“…The Cadia/Calpurnia clade is sister to Sophora, a genus with papilionoid flowers (Tucker, 1994). However, in several Sophora species and other zygomorphic papilionoids (Tucker, 1984(Tucker, , 1985(Tucker, , 1987(Tucker, , 1989(Tucker, , 1993(Tucker, , 1994Tucker and Stirton, 1991) flowers appear radially symmetrical at midstage. Zygomorphy is expressed late in ontogeny in all of these taxa.…”
Section: Discussionmentioning
confidence: 99%
“…The Cadia/Calpurnia clade is sister to Sophora, a genus with papilionoid flowers (Tucker, 1994). However, in several Sophora species and other zygomorphic papilionoids (Tucker, 1984(Tucker, , 1985(Tucker, , 1987(Tucker, , 1989(Tucker, , 1993(Tucker, , 1994Tucker and Stirton, 1991) flowers appear radially symmetrical at midstage. Zygomorphy is expressed late in ontogeny in all of these taxa.…”
Section: Discussionmentioning
confidence: 99%
“…C. fasciulata produces floral meristems from the developing I2, accompanied by the outgrowth of other organs including bracts, bracteoles, additional axillary flowers, and vegetative shoots. In contrast, papilionoids, specifically the well-studied garden pea (Pisum sativum), produce flowers and suppress the outgrowth of additional organs (Tucker, 1989;Singer et al, 1990;Fig. 4).…”
Section: Floweringmentioning
confidence: 99%
“…2). Papilionoid flowers have strong bilateral symmetry, a derived condition within the angiosperms (Tucker, 1989). Comparisons of the floral transcriptomes of Chamaecrista and papilionoid legumes may offer clues to the origins of bilateral symmetry within the legumes.…”
mentioning
confidence: 99%
“…The whole-genome sequencing project has been carried out [12], and several L. japonicus Chr. TM0123 TM0050 TM0193 TM0117 TM0001 TM0122 TM0134 TM0065 TM0225 TM0124 TM0020 TM0002 TM0436 TM0190 TM0155 TM0142 TM0049 TM0203 TM0127 TM0288 TM0182 TM0247 TM0030 TM0046 TM0218 TM0095 TM0048 TM0062 TM0072 TM0146 TM0014 TM0057 TM0140 TM0066 TM0336 TM0314 * [17][18][19]. Our previous work has demonstrated that L. japonicus is an excellent system to dissect the components in the pathway to control floral development [20,21].…”
Section: Introductionmentioning
confidence: 99%